2014
DOI: 10.1016/j.freeradbiomed.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of obesity and insulin resistance by nitric oxide

Abstract: Obesity is a risk factor for developing type 2 diabetes and cardiovascular disease and has quickly become a world-wide pandemic with few tangible and safe treatment options. While it is generally accepted that the primary cause of obesity is energy imbalance, i.e., the calories consumed are greater than are utilized, understanding how caloric balance is regulated has proven a challenge. Many “distal” causes of obesity, such as the structural environment, occupation, and social influences, are exceedingly diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
202
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(224 citation statements)
references
References 353 publications
(329 reference statements)
10
202
1
11
Order By: Relevance
“…Lower NOS3 abundance is found in both adipose tissue and skeletal muscle of obese humans [30,31]. Decreased NOS3 expression commonly occurs in obese and diabetic states [32]. Beyond changes in expression, the NO-producing activity of NOS3 is diminished in metabolic disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…Lower NOS3 abundance is found in both adipose tissue and skeletal muscle of obese humans [30,31]. Decreased NOS3 expression commonly occurs in obese and diabetic states [32]. Beyond changes in expression, the NO-producing activity of NOS3 is diminished in metabolic disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this regards there are also another reports indicated that elevation of nitric oxide activity is a mechanism for lower incidence of arterial hypertension in females [4,8]. Shangjian, et al also in a study reporting higher levels of serum nitric oxide level as a compensatory mechanism in insulin resistant rats comparing with control group [9]. Other studies in healthy human subjects also indicating a direct relationship between nitric oxide production in endothelial vascular cells and insulin sensitivity [10].…”
Section: Introductionmentioning
confidence: 84%
“…Its therapeutic effects are produced mainly by the inhibition of norepinephrine (NE) and serotonin (5-hydroxytryptamine, 5-HT) reuptake at neuronal synapse sites in the Central Nervous System (CNS). This inhibition causes an increase in the synaptic concentration of these substances and consequently an increase in the feeling of satiety and energy expenditure and a resultant decrease in food intake (Lechin et al, 2006;Eroglu et al, 2009;Sansbury BE and Hill BG, 2014). After absorption, Sibutramine is metabolized by the hepatic Cytochrome P450 enzymes, forming the pharmacologically active metabolites, M1 and M2, which are responsible for the resultant hypophagic effect and subsequent weight-loss (Hwang IC et al, 2014;Luque and Rey 2002;Padwal and Majumdar 2007).…”
Section: Introductionmentioning
confidence: 99%